2003
DOI: 10.1038/sj.ijo.0802431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary restraint during and following pegylated recombinant leptin (PEG-OB) treatment of overweight men

Abstract: OBJECTIVE:To examine the effect of dietary restraint during and following pegylated recombinant leptin (PEG-OB protein) treatment in overweight men. DESIGN: A randomized double-blind placebo-controlled trial in 24 overweight men (BMI: 28.870.3 kg/m 2 ; age: 34.870.9 y). PEG-OB protein (80 mg) or placebo was administered subcutaneously weekly for 6 weeks, combined with a 2.1 MJ/day energy restriction program. Dietary restraint was determined by the Three-Factor Eating Questionnaire before and after treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
2
27
1
Order By: Relevance
“…37 A period of 6-week treatment by leptin/VLCD, similarly to our 4-week VLCD trial, 5 lead to an increase in cognitive restraint score and to a significant decrease in both disinhibition and hunger scores. The decrease in hunger score during the leptin treatment was Weight loss predictors in sibutramine treated obese women V Hainer et al positively related to body weight loss.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…37 A period of 6-week treatment by leptin/VLCD, similarly to our 4-week VLCD trial, 5 lead to an increase in cognitive restraint score and to a significant decrease in both disinhibition and hunger scores. The decrease in hunger score during the leptin treatment was Weight loss predictors in sibutramine treated obese women V Hainer et al positively related to body weight loss.…”
Section: Discussionmentioning
confidence: 53%
“…However, the decrease in disinhibition score during the treatment period positively correlated with the weight loss in the placebo group and not in the leptintreated group. 37 Among the recorded changes in behavioral and nutritional parameters over the study, our results revealed the unique role of change in disinhibition score, which remained the sole significant factor related to the BMI decrease at month 12. The association of sibutramine-induced weight loss with a decline in disinhibition might be related to the previously shown positive impact of sibutramine treatment on obesityrelated health risks.…”
Section: Discussionmentioning
confidence: 64%
“…The authors suggested this was due to decreased insulin-mediated glucose metabolism in adipose tissue, and that decreased postprandial exposure of leptin resulting from a fat bolus could be adipogenic (Havel et al, 1999), citing the hyperphagia and gross obesity resultant in humans from genetic impairment of leptin production (Montague et al, 1997). Whether a decrease in circulating leptin over 24 h may represent an adverse risk for obesity remains controversial and recombinant leptin weight loss therapy in hyperleptinaemic obese subjects has been met with limited success (Hukshorn et al, 2002;Fogteloo et al, 2003;Lejeune et al, 2003;Wong et al, 2004). It has been suggested that the role of leptin is not prevention of obesity, rather a response to low-energy availability (Havel, 2004) such that during starvation leptin falls triggering an increase in hunger .…”
Section: Discussionmentioning
confidence: 99%
“…Initial attempts to utilize leptin as a monotherapy for obesity included using supraphysiological doses of leptin (75,103,147); however, data from these trials revealed modest, if any, weight loss and with significant variability among the participants. In a small, proofof-concept, phase II clinical trial, Heymsfield et al (103) administered leptin in escalating doses to obese participants for up to 24 wk.…”
Section: Leptin Excess Due To Leptin Resistance or Tolerance In Humanmentioning
confidence: 99%